Speciation forms of phosphorus in bottom sediments of three selected anthropogenic reservoirs with different trophy degree - Kostecki Maciej; Janta-Koszuta Krystyna; Stahl Katarzyna; Łozowski Bartosz (Archives of Environmental Protection, 2017)
The study presents the results of the research into different phosphorus forms in the bottom sediments of anthropogenic limnic ecosystems i.e. the reservoirs of Pławniowice, Rybnik and Goczałkowice (SP). The bottom sediments of dam reservoirs were investigated by chemical extraction procedure for phosphorus forms. The lowest value of the mean AAP form percentage in the Pławniowice bottom sediments reflected the effect of reclamation with the hypolimnetic removal that had been conducted in the reservoir since 2003. The highest percentage of the RDP form (2%) was found in the Goczałkowice bottom sediments. The order of the specific speciation forms in the bottom sediments of the examined reservoirs was: